"Something of an Adventure": Postwar NIH Research Ethos and the Guatemala STD Experiments. Issue 3 (1st October 2013) - Spector‐Bagdady, Kayte; Lombardo, Paul A.
<x xml:space="preserve">Abstract</x> The STD experiments in Guatemala from 1946–1948 have earned a place of infamy in the history of medical ethics. But if the Guatemala STD experiments were so "ethically impossible, " how did the U.S. government approve their funding? Although much of the literature has targeted the failings of Dr. John Cutler, we focus on the institutional context and research ethos that shaped the outcome of the research. After the end of WWII, Dr. Cassius Van Slyke reconstructed the federal research contracts process into a grant program. The inaugural NIH study section recommended approval of the Guatemala STD experiments at its first meeting. The funding and oversight process of the Guatemala research was marked with serious conflicts of interest and a lack of oversight, and it was this structure, as opposed to merely a maleficent individual, that allowed the Guatemala STD experiments to proceed. We conclude that while current research regulations are designed to prevent the abuses perpetrated on the subjects of the Guatemala STD experiments, it takes a comprehensive understanding of research ethics through professional education to achieve the longstanding ideal of the responsible investigator, and ensure ethical research under any regulatory scheme.